2019
DOI: 10.1149/2.0102001jes
|View full text |Cite
|
Sign up to set email alerts
|

Editors' Choice—Simulation of Copper Electrodeposition in Through-Hole Vias

Abstract: Copper electrodeposition processes for filling metallized through-hole (TH) and through-silicon vias (TSV) depend on spatially selective breakdown of a co-adsorbed polyether-chloride adlayer within the recessed surface features. In this work, a co-adsorption-dependent suppression model that has previously captured experimental observations of localized Cu deposition in TSV is used to explore filling of TH features. Simulations of potentiodynamic and galvanostatic TH filling are presented. An appropriate applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…By COMSOL simulation, Moffat et al [44] . reported that the power lines at the mouth of THs were denser than that at the interior wall.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By COMSOL simulation, Moffat et al [44] . reported that the power lines at the mouth of THs were denser than that at the interior wall.…”
Section: Resultsmentioning
confidence: 99%
“…By COMSOL simulation, Moffat et al [44] reported that the power lines at the mouth of THs were denser than that at the interior wall. This infers that the electro-reduction potential at the mouth will be more negative than that at the middle of THs.…”
Section: Ths Copper Electronic Electroplatingmentioning
confidence: 99%
“…2,43,66,67 For copper electroplating, the difference between active and passive deposition can be amplified to great effect by adding hydrophobic secondary structure to the polyether suppressor, e.g., poloxamers, poloxamines, etc. 2,4,68 Given a modest concentration of either the polyether or halide, critical behavior manifests during suppression breakdown when transport and/or kinetic effects limit the ability of the passive state to reform. For highly conductive electrolytes, the breakdown to fully activated deposition can be particularly sharp and not easily controlled by potentiostatic regulation.…”
Section: Leveler−accelerator Interactionsmentioning
confidence: 99%
“…For higher aspect ratio and larger-scale TSV and PCB features with dimensions similar to or greater than those of the hydrodynamic boundary layer, transport and the kinetics of adsorption, desorption, and/or consumption on advancing interfaces play an important role in feature filling. This is particularly true for a subset of accelerator-free additive systems that display critical behavior where positive feedback, from the disruption of the suppressor phase by metal deposition, results in the system jumping from the passive to the active state over a narrow potential window. ,,, For copper electroplating, the difference between active and passive deposition can be amplified to great effect by adding hydrophobic secondary structure to the polyether suppressor, e.g., poloxamers, poloxamines, etc. ,, Given a modest concentration of either the polyether or halide, critical behavior manifests during suppression breakdown when transport and/or kinetic effects limit the ability of the passive state to reform. For highly conductive electrolytes, the breakdown to fully activated deposition can be particularly sharp and not easily controlled by potentiostatic regulation. , Significantly, the presence of substantial ohmic resistance will attenuate the criticality whereby, for a fixed applied potential, the driving force is distributed dynamically between the interface potential, which determines the rate of metal deposition and additive adsorption, and the ohmic losses in the electrolyte.…”
Section: Larger Feature Sizes and Critical Phenomenamentioning
confidence: 99%
See 1 more Smart Citation